Evaluation of insulin-like growth factor-1 in apparently healthy infants and prepubertal Egyptian children with different nutritional statuses - Hanan Mina Fouad; Amal Ahmed Mohamed; Nashwa Adel; Mohamed Abdulhay; Iman Khalifa; Randa Ibrahim; Naglaa Elsalway; Ghada Maher Thabet; Karima Nasraldin; Ingy Maher El-Hefny; Marwa S. Abd El-raouf; Dalia Ghareeb (BMC Pediatrics)
Abstract Objectives to estimate insulin-like growth factor-1 (IGF-1) levels in apparently healthy infants and prepubertal children and compare results among different nutritional statuses. Methods Our cross-sectional work is a sub-study of a screening project for anemia and nutritional status. We included 252 apparently healthy infants and children with a mean age of 3.7 ± 1.3 years (1.1–6.6), with equal gender distribution. Data retrieved included breastfeeding and anthropometric measures. We tested the stored blood samples for IGF-1 levels. The sample size was reached when all kits were consumed. Results abnormal anthropometric measures were detected in 32.9%, either a single or multiple, and 86.5% were breastfed. Girls had significantly higher serum IGF-1 levels than boys (P: <0.001), which was noticeable in girls with abnormal nutritional status detected with anthropometry. Breastfeeding showed no significant association with IGF-1 levels. No significant difference was observed between IGF-1 levels between children with normal versus those with abnormal growth measures. Children with overweight or obesity had significantly lower IGF-1 than children with other body mass index (BMI) categories. Serum IGF-1 levels correlated positively with arm muscle area Z scores in infants and toddlers and weight and BMI Z scores in children between three and four. Also, IGF-1 correlated positively with the triceps skinfold Z score and arm muscle area Z score between four and five. Conclusions Among studied infants and prepubertal children, serum IGF-1 was significantly higher in girls than boys and was considerably lower in children with overweight or obesity. Breastfeeding showed no association with IGF-1 levels.